2022
DOI: 10.1111/aej.12627
|View full text |Cite
|
Sign up to set email alerts
|

Surface roughness and cyclic fatigue resistance of reciprocating and novel rotary instruments after use in curved root canals

Abstract: This study evaluated surface wear and resistance to fracture of reciprocating and novel rotary instruments after use in curved canals. Twenty new instruments (n = 5/each group): Reciproc Blue, WaveOne Gold, XP‐endo Shaper (XPS) and TruNatomy were used twice for the instrumentation of simulated curved canals in plastic blocks. The instrumentation was performed according to the manufacturer's instructions at body temperature. Surface roughness was evaluated, using a profilometer, before instrumentation and twice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…The length of the files was adjusted to 19mm using the file stoppers to standardize the instrument placement inside the canals for all files (20,28) The results of this study showed that the cyclic fatigue values of all the reciprocating file systems; WaveOne Gold, WaveOne and EdgeOne, were greater than that of the rotational motion file system EdgeFileX7. These findings were in accordance with Castello-Escriva et al 2012 (30) , Kiefner et al 2014 (31) , Alcalde et al 2018 (32), Merima et al 2022 (6) . and Bueno et al 2020 (33) who showed that reciprocating motion reduces the cyclic fatigue resistance of endodontic files thus lowering the probability of instrument separation inside the root canal.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The length of the files was adjusted to 19mm using the file stoppers to standardize the instrument placement inside the canals for all files (20,28) The results of this study showed that the cyclic fatigue values of all the reciprocating file systems; WaveOne Gold, WaveOne and EdgeOne, were greater than that of the rotational motion file system EdgeFileX7. These findings were in accordance with Castello-Escriva et al 2012 (30) , Kiefner et al 2014 (31) , Alcalde et al 2018 (32), Merima et al 2022 (6) . and Bueno et al 2020 (33) who showed that reciprocating motion reduces the cyclic fatigue resistance of endodontic files thus lowering the probability of instrument separation inside the root canal.…”
Section: Discussionsupporting
confidence: 86%
“…The use of NiTi rotary files for root canal preparation has increased owing to their unquestionably favorable properties but unfortunately, they have the drawback of unpredicted fracture. Fatigue fracture happens due to repetitive tensile and compressive stresses at the point of maximum flexure of an instrument rotating in a curved canal and the instrument may not display any sign of fatigue or deformation prior to its use (3)(4)(5)(6) .…”
Section: Introductionmentioning
confidence: 99%
“…The limitation of this study was that the mechanical tests and simulated canal shaping were performed at 22 • C. The main phase of XP-endo Shaper changes from martensite to austenite on heating from room temperature to body temperature. XP-endo Shaper, which is composed of Max-Wire NiTi alloy, display optimal properties only at higher temperatures (37 • C) [34]. Therefore, experiments at body temperature are necessary to observe the mechanical properties of the XP-endo Shaper files used in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…One recent study by Ertugrul et al [ 18 ] reported a higher cyclic fatigue life of Rotate compared to MTwo with a single curvature of 60° and proposed that surface topography is important and may affect the cyclic fatigue resistance. Additionally, it has been claimed that the fatigue life of endodontic files may be shortened with an increase in surface roughness [ 19 , 20 ]. Thus, it is important to perform a topographical analysis of the instrument to explain its influence on the instrument’s resistance [ 16 ].…”
Section: Introductionmentioning
confidence: 99%